Loss of myocardial protection against myocardial infarction in middle-aged transgenic mice overexpressing cardiac thioredoxin-1 - D'annunzio, Verónica (2016)
Thioredoxin-1 (Trx1) protects the heart from ischemia/reperfusion (I/R) injury. Given that the age at which the first episode of coronary disease takes place has considerably decreased, life at middle-aged (MA) emerges as a new field of study. The aim was determine whether infarct size, Trx1 expression and activity, Akt and GSK-3β were altered in young (Y) and MA mice overexpressing cardiac Trx1, and in a dominant negative (DN-Trx1) mutant of Trx1. Langendorff-perfused hearts were subjected to 30 minutes of ischemia and 120 minutes of reperfusion (R). We used 3 and 12 month-old male of wild type (WT), Trx1, and DN-Trx1. Trx1 overexpression reduced infarct size in young mice (WT-Y: 46.8±4.1% vs. Trx1-Y: 27.6±3.5%, p < 0.05). Trx1 activity was reduced by 52.3±3.2% (p < 0.05) in Trx1-MA, accompanied by an increase in nitration by 17.5±0.9%, although Trx1 expression in transgenic mice was similar between young and middle-aged. The expression of p-Akt and p-GSK-3β increased during reperfusion in Trx1-Y. DN-Trx1 mice showed neither reduction in infarct size nor Akt and GSK-3β phosphorylation. Our data suggest that the lack of protection in Trx1 middle-aged mice even with normal Trx1 expression may be associated to decreased Trx1 activity, increased nitration and inhibition of p-Akt and p-GSK-3β.